A collection of several tracts of the Right Honourable Edward, Earl of Clarendon - Clarendon, Edward Hyde ((Library of English literature, LEL 11551)., 1727)
A discourse by way of vindication of my self from the charge of high-treason : with which I was charged by the House of Commons November 1667 -- Reflections upon several Christian duties, divine and moral : by way of essays -- A dialogue between an old courtier, an old lawyer, an old soldier, an old country gentleman, and an old alderman, of the want of respect due to age -- A dialogue between the same persons and a bishop concerning education -- Contemplations and reflections upon the Psalms of David ...